7T MRI for neurodegenerative dementias in vivo: a systematic review of the literature. Issue 7 (4th March 2017) - McKiernan, Elizabeth Frances; O'Brien, John Tiernan
Abstract : The spatial resolution of 7T MRI approaches the scale of pathologies of interest in degenerative brain diseases, such as amyloid plaques and changes in cortical layers and subcortical nuclei. It may reveal new information about neurodegenerative dementias, although challenges may include increased artefact production and more adverse effects. We performed a systematic review of papers investigating Alzheimer's disease (AD), Lewy body dementia (LBD), frontotemporal dementia (FTD) and Huntington's disease (HD) in vivo using 7T MRI. Of 19 studies identified, 15 investigated AD (the majority of which examined hippocampal subfield changes), and 4 investigated HD. Ultrahigh resolution revealed changes not visible using lower field strengths, such as hippocampal subfield atrophy in mild cognitive impairment. Increased sensitivity to susceptibility-enhanced iron imaging, facilitating amyloid and microbleed examination; for example, higher microbleed prevalence was found in AD than previously recognised. Theoretical difficulties regarding image acquisition and scan tolerance were not reported as problematic. Study limitations included small subject groups, a lack of studies investigating LBD and FTD and an absence of longitudinal data. In vivo 7T MRI may illuminate disease processes and reveal new biomarkers and therapeutic targets. Evidence from AD and HD studies suggest that other neurodegenerative dementias would also benefit from imaging at ultrahigh resolution.